Preparation and evaluation of polyelectrolyte complexes for oral controlled drug delivery - Srinivas, L; Murthy, K V Ramana (Asian Journal of Pharmaceutics (AJP), 2014)
The electrostatic interaction between oppositely charged polyelectrolytes leads to formation of insoluble polyelectrolyte complexes in aqueous medium. The polyelectrolyte complexes formed between a polyacid and a polybase are little affected by the pH variation of the dissolution medium. In the present study attempts were made to prepare polyelectrolyte complexes of polyvinyl pyrrolidone (polybase) and carbopol (polyacid) into which diclofenac sodium is incorporated and studied for its controlled release.The polyelectrolyte complexation was evaluated by pH, conductivity, Fourier transformed infrared spectroscopy, and X-ray difractometry. The dried polyelectrolyte complexes were also evaluated for micromeritic properties and drug release kinetics. Selected PECs were compressed into tablets and compared with commercial SR product for drug release.The tablets showed comparable results with commercial SR product following zero-order release, and drug release is by erosion as well as the diffusion mechanism. Promising results were obtained suggesting the application of these polyelectrolyte complexes in the design of controlled release systems.